2016
DOI: 10.3892/ijmm.2016.2689
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide inhibits colon cancer progression through downregulation of the Notch pathway and upregulation of the tumor suppressor miR-200 family

Abstract: Colorectal cancer (CRC) is among the most frequent causes of cancer-related deaths worldwide. Thus, there is a need for the development of new therapeutic approaches for the treatment of CRC. Accumulating evidence has revealed that niclosamide, an anthelminthic drug, exerts antitumor activity in several types of cancer, including colon cancer. However, the underlying molecular mechanisms responsible for the effects of this drug remain elusive. Previous studies have shown that the aberrant Notch signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…Irinotecan may penetrate and injure normal tissues, including mucosal membranes and results in unwanted side effects, such as diarrhea and vomiting . MicroRNA also shows the disadvantages of rapid degradation and poor cellular uptake . Hence, it is necessary to develop a pH‐sensitive and tumor‐targeting delivery system with good penetration for irinotecan and miR to improve the treatment of advanced CRC, as indicated in Figure A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irinotecan may penetrate and injure normal tissues, including mucosal membranes and results in unwanted side effects, such as diarrhea and vomiting . MicroRNA also shows the disadvantages of rapid degradation and poor cellular uptake . Hence, it is necessary to develop a pH‐sensitive and tumor‐targeting delivery system with good penetration for irinotecan and miR to improve the treatment of advanced CRC, as indicated in Figure A.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of miR‐200 alone was not sufficient as a single anticancer agent. Additionally, there are obstacles for miR delivery into cells, including rapid degradation in the systemic circulation, fast detection by the immune system, low cellular uptake, and poor endosomal escape . Hence, we designed solid lipid nanoparticles (SLN) and liposomes (Lip) to specifically and separately deliver hsa‐miR‐200c‐3p and irinotecan.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported on the niclosamide enhances cytotoxicity on various cancers, including oral cancer, lung cancer, colon, thyroid, cervix, ovarian, kidney, and prostate cancers, via STAT3, EGFR/PI3K/Akt, RANKL Wnt, mTOR, HIF‐1α/VEGF, Ras, c‐myc, and Notch signal pathways and mitochondria dysfunction 11, 12, 13, 14, 26, 27, 28, 29, 30, 31, 32, 33. Cancer cell upregulates other important downstream genes such as STAT3, which contributes to cell proliferation, cell survival, and angiogenesis in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Niclosamide is an anti-helminthic drug introduced in the 1950's, and has been used to treat parasitic infections in millions of patients worldwide [8]. It has been shown to effect a number of host cellular signaling pathways, including Wnt [9], Notch [10], mTOR, NF-κB [11], and STAT3 [12]. This broad activity has led to its evaluation as a therapeutic agent for a number of cancers, including breast, colon, ovarian, prostate, and others [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%